Effects of the faecal stream and stasis on the ileal pouch mucosa. Issue 10 (October 1991) - de Silva, H J; Millard, P R; Soper, N; Kettlewell, M; Mortensen, N; Jewell, D P
Abstract : This study aimed to investigate the effects of the faecal stream and stasis on the mucosa of ileal pouches. Nine patients were followed up. Two pouch biopsy specimens were obtained from each at the time of pouch formation, ileostomy closure, and three, six, and 12 months after operation. None developed pouchitis. Two pouch biopsy specimens each were also obtained from 20 patients (six with pouchitis), whose pouches had been functioning for at least a year and in whom pouch evacuation was assessed by radioisotope labelled artificial stool. Biopsy specimens were assessed for the degree of acute and chronic inflammation, mucin type (high iron diamine-alcian blue stain), a morphometric index of villous atrophy (villous height:total mucosal thickness), and crypt cell proliferation (using the monoclonal antibody Ki67). Mean values from the two biopsy specimens were obtained for each parameter. After three months of pouch function, the scores for acute and chronic inflammation, the degree of sulphomucin, and crypt cell proliferation were significantly higher, and the index of villous atrophy was significantly lower (indicating a greater degree of villous atrophy), than at pouch formation or at ileostomy closure. The values at pouch formation and ileostomy closure were similar. For all parameters, the changes seen at six and 12 months were not significantly different from those at three months. There was no significant correlation between the efficiency of pouch evacuation and any of the mucosal changes. It is concluded that exposure to the faecal stream is necessary for changes to take place in the pouch mucosa, although the amount of stasis, as measured by radioisotopic evacuation studies, seems to be irrelevant. The mucosal changes occur soon after ileostomy closure and then remain stable for at least one year.